Direct effect of radiation on the peripheral nerve in a rat model. Issue 4 (August 2014) - Okuhara, Yukako; Shinomiya, Rikuo; Peng, Feng; Kamei, Naosuke; Kurashige, Takashi; Yokota, Kazunori; Ochi, Mitsuo
Abstract Radiation neuropathy is one of the severe complications of radiotherapy. Entrapment neuropathy, caused by surrounding soft tissue fibrosis induced by radiation, plays a key role in the onset of this neuropathy. Meanwhile, the pathophysiology of the direct effect of radiation on the peripheral nerve is not yet fully understood. The aim of this study is to investigate the direct effects of radiation on rat sciatic nerves that are isolated from surrounding soft tissue. In the radiation group (R group), only the exposed sciatic nerve was irradiated with 90 Gy X-radiation. In the sham group (S group), the surgical procedures were completed without radiation. The sciatic functional index (SFI) result demonstrated no statistical differences between the R group and S group. However, even though the surrounding soft tissue was not irradiated, the macroscopic and histological findings of the R group at 24 weeks after radiation showed scar formation around the radiated nerve. These findings on radiation neuropathy indicate that neurohumoral factors derived from the radiated nerve itself may cause fibrosis. The electromyographic and histological examination showed axonal degeneration in the R group. Furthermore, the axon diameter and axon packing density in the R group demonstrated the axonal degeneration, even though it was 0.5 cm more proximal to the radiated portion than the axon packing density in the S group. This appearance was assumed to be "dying-back" neuropathy. It is believed that this study is a first step toward identifying an accurate pathophysiology for intractable radiation-induced peripheral neuropathy.